Changes in soil properties under tree species - SINGH, I S; AWASTHI, O P; SINGH, R S; MORE, T A; MEENA, S R (The Indian Journal of Agricultural Sciences, 2012)
A study was conducted to study the effects of ber (Ziziphus mauritiana Lamk), drumstick (Moringa olerifera Lam), karonda (Carissa congesta Wt.) and khejri (Prosopis cineraria L. Druce) on the physical and chemical properties of soil at different depths (0–15, 15–30, 30–45 and 45–60 cm). The increase in the porosity and water-holding capacity and decrease in the bulk density (of subsurface soils) in the sites under plantations were marginal, when compared to open sites. There was slight decrease in the pH of soil under vegetated area, whereas no appreciable change in EC was observed. There was an appreciable increase in the organic carbon (0.04 to 0.13%) and available nitrogen content (69 to 100 kg/ha) in the sites under vegetation. Fruit plants, particularly ber and drumstick growing in the arid region indicated the process of deposition of bases such as Ca and Mg in the surface layers from lower strata. Overall results showed that exchangeable cations such as Ca, Mg, and Na and available P and K have depicted a poor potential activity in the maintenance of fertility which is affected by the young nature of plantation. The increase/decrease of soil properties due to the influence of plantation was more in surface (0–15 cm) and subsurface (15–30 cm) than in the sub-surface layers of 30–45 and 45–60 cm. The results obtained from the physical and chemical analyses indicated that among the four different fruit plantations, ber recorded substantial improvement and maintenance in soil fertility followed by drumstick. The nutrient return through litter fall followed the order K > N > Ca in Z. mauritiana and M. olerifera and N > Ca > K, Ca > N > K in C. congesta and cineraria respectively. The soils belong to the order Entisol and the calcareous pH is well adopted for the plantation of these fruit trees.